The foreign investment screening process in LDCs : the case of Colombia, 1967-1975 - Lombard, François J. (Boulder, Colo. : Westview Press, 1979)
The purpose of the study in the this book was to design a model which explains why a nation-state regulates the entry of foreign investment. Also to describe the dynamics of this regulating process over time, and to test the explanatory and predictive properties of the model for a specific country, Colombia.
Bibliography: p. 160-171.
usc 25/05/18
Loans
Keywords: Investments, Foreign; Investments, Foreign--Law and legislation; Developing countries; Colombia